Climate-related displacement, impoverishment and healthcare accessibility in mainland Bangladesh. Issue 2 (3rd May 2020) - Haque, Rabiul; Parr, Nick; Muhidin, Salut
ABSTRACT: This paper examines the experiences of people displaced internally by climate-related factors in mainland Bangladesh, one of the world's most climate-vulnerable countries. The data derives from a representative survey of 1, 200 households drawn equally from displacement-susceptible areas and areas without climate-related displacement. Comparisons are drawn on the basis of four variables: the displaced versus the non-displaced; before displacement versus after displacement; people displaced suddenly versus those displaced gradually; and the frequency of past displacement. The displaced experience multiple disadvantages, including reduced land ownership and reduced access to electricity, sanitary toilets and healthcare services. The disadvantage is greater following sudden displacement and among those who have been displaced multiple times. The impact on the time and cost of accessing healthcare are greater after displacement. The disadvantage of the displaced, thus, is a function of interactions between exposure to natural disaster, impoverishment and lack of access to health services.